Grassland ecosystem health and biomass in protected natural areas for Mexican prairie dog (Cynomys mexicanus) in Nuevo Leon, Mexico - Zaragoza-Quintana, Elisa Paulina; Cotera Correa, Mauricio; Scott Morales , Laura Magdalena; Pando Moreno, Marisela; Estrada Castillón, Andrés Eduardo; González Rodríguez, Humberto (Acta Universitaria, 2022)
In Nuevo Leon, Mexico, three protected natural areas (PNA) have been declared to conserve Cynomys mexicanus; however, agricultural activities are still present within these areas, in conjunction with a lack of information related to their habitat condition. In this study, grassland health and biomass production were evaluated in three protected areas (la Trinidad, la Hediondilla and Llano la Soledad) to determine their functionality. The ecosystem health of La Hedionadilla was deteriorated, and its core zone showed the most critical functional status; additionally, it showed the highest annual production of biomass (0.53 Mg/ha-1) due to land-use change and invasive vegetation. The productive activities in Llano La Soledad are mainly dedicated to cattle raising, and although the biomass production was lower (0.14 Mg/ha-1), it showed the best health condition because its surface is restricted. The deteriorated health of grassland is a threat to Cynomys mexicanus and the biodiversity of its ecosystem.